Keunikan Bahasa Pola Pembelajaran melalui Komunikasi Keluarga untuk Mendukung Anak Sebagai Atlet Esport - Syarnubi, Kenn Lazuardhi; Lang, Jouns Candy Felice; Marta, Rustono Farady; Santoso, Nobertus Ribut; Misnawati, Desy (Universitas Nusantara PGRI Kediri, 2020)
Esports have drew considerable attention from Indonesian teenagers. Some of them enjoy them as entertainment; meanwhile, others seriously participate in the esports to gain achievement and earn income. Family communication and the role of parents are critical in providing support to their children to optimize their ability in the esport. This study aims to identify the family's role in learning patterns through various languages ​​conveyed by parents to their children to excel in the esport field. The method employed in this study was semiotic by investigating signs (language used by parents of esport athletes) derived from a YouTube channel content of Bigetron E-sport functioned as the unit of analysis. The data were analyzed and classified into six categories of the sign developed by Thomas Albert Sebeok. The results revealed that the parents’ support conveyed through language uniqueness of learning patterns to their children in pursuing a career in esports is essential to stimulate the children’s mindset and achievements.